IMPLEMENTASI PROGRAM PEGUATAN NILAI-NILAI KEAGAMAAN ISLAM DI SD IT MUJAHIDUL AMIN PALANGKA RAYA - Muhammad Lutfhi Yahya; Nurul Hikmah; Syahmidi Syahmidi (Jurnal Manajemen Pendidikan, 2026)
Strengthening Islamic religious values in elementary schools plays a strategic role in shaping students’ character and moral development from an early age. This study aims to analyze the implementation of Islamic religious value strengthening programs at SD IT Mujahidul Amin Palangka Raya. The research employs a qualitative approach involving school leaders, teachers, and students who are directly engaged in the implementation of religious programs. Data collection was conducted through interviews, observations, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data analysis was carried out through data condensation, data presentation, and conclusion drawing. The findings show that the strengthening of Islamic religious values is implemented in a structured and sustainable manner through three main programs: the 1 Day 1 Goodness Program, the Code of Conduct (COC) Program, and the Amaliyah Worship Enrichment Program. These programs instill sincerity, discipline, social morality, and spiritual awareness through daily habituation, reflective discipline, and continuous worship guidance, including during school holidays, with parental involvement. Overall, synergy between school and family effectively fosters religious character, discipline, and commendable morals among elementary school students, while offering a model for Islamic character education at the primary level.